Zoning atmospheric Hazards in North West of Iran - batool zeinali; sima khalili; saideh eiyni (تحقیقات کاربردی علوم جغرافیایی)
The aim of current research is atmospheric hazards climate zoning in Iran Northwest. So meteorological organization data were used in cases such as mean temperature , minimum temperature , maximum temperature, precipitation in monthly and daily scale for 13 synoptic stations in range of East Azerbaijan province, West Azerbaijan province) and Ardebil province during 26 years. (1990-2015) in this research , it was investigated 10 main atmospheric hazards such as famine or drought , hailstone,, heavy snow , thunder storm, severe precipitation, margin precipitation , blizzard , fogging , dust storm in range of Northwest bound. Then happening frequency maps were prepared with separating form for hazards by using Geographic information system. (GIS) Also spatial zoning maps were prepared for every class. Finally by combining all of hazards investigation; it was prepared Northwest region atmospheric hazards extensive map. Results show that, East, Southeast, center and West parts in Northwest region are located among most hazard zones based on happening frequency. But Northeast parts and zones have the least hazards. Also results express that blizzard and dust storm are main atmospheric hazards at Northwest regionThe highest hazard frequency in Northwest region relate to blizzard with 4148 hazards during 1990-2015 study period. The highest blizzard frequency in Ahar station is observed with 514 hazards. The second hazard in Northwest relate to dust phenomenon with 1948 cases. The highest frequency of mentioned case was observed in Maragheh station with 410 hazards. The third case in Northwest relate to thunder storm phenomenon with 1773 hazards. The sixth case relate to icing phenomenon with 1315 hazards meaning. The highest icing frequency is observed in Khalkhal station with 144 hazards. The seventh case relate to hailstone phenomenon at Northwest with 341 hazards. The highest of hailstone frequency is observed in Maragheh station with 56 hazards. The eighth case relate to fogging phenomenon with 333 hazards. The highest of fogging is observe in Ahar station with 135 hazards. The ninth case relate to famine or drought phenomenon at Northwest with 168 hazards. The highest of famine or drought frequency is observed in Urmia and Ardebil stations with 16 hazards totally. The highest margin precipitation is observed in Parsabad station with 19 hazards. The lowest frequency of margin precipitation relate to Makou and Khalkhal stations with 4 hazards totally.